Mammary metaplastic carcinoma: a very rare case with review of literature - Tabrez, Md. Omar; Aziz, Md. Tabrez (International Surgery Journal, 2017)
Metaplastic carcinoma of breast is a rare neoplasm. Although it is a tumor of ductal type, the predominant component may have an appearance other than the glandular pattern and usually runs an aggressive course. We report the case of a 36-year-old female patient with a left breast lump. Neither imaging nor fine needle aspiration biopsy was crucial in achieving a diagnosis. The patient underwent MRM with axillary clearance. In consideration of the lymph node status, the patient was subjected to radiotherapy and adjuvant chemotherapy. The patient has been disease free for 2 years now. Literature review has suggested metaplastic carcinoma of breast is rare neoplasm and diagnosis is difficult to make, hence should be managed aggressively with surgery followed by radiotherapy and adjuvant chemotherapy.